An empirical analysis of administrative economic efficiency in Sabah local government: A dea application Siew King Ting, Brian Dollery and Rene Villano - Ting, Siew King; Dollery, Brian; Villano, Rene (Universiti Teknologi MARA Cawangan Sarawak, 2017)
Malaysian local government reform has been addressed through various public policies aimed at improving its performance over the decades. An important question which arises is whether these technological and management programs have translated into performance gains, particularly in the corporate centres of local authorities (LAs). Using a panel data of two inputs and four outputs from 2000 to 2012, a two-stage double bootstrap Data Envelopment Analysis (DEA) method is employed to estimate administrative technical efficiency (TE) in the corporate centres of 17 LAs in the Malaysian state of Sabah. The results showed an overall inadequate mean of TE scores and minor fluctuations in TE scores over the years under analysis, illustrating the rigidity of management performance. On average, the LAs recorded TE scores of 0.52, which implied that the LAs should be able to increase output by 48% while maintaining the same amount of input. The big urban LAs performed better with the TE scores of 0.60; while the small urban LAs recorded lower TE scores of 0.43. Further analysis demonstrated that the environmental variable, urban population bore a negative relationship to the TE scores. Several public policy recommendations are proposed